RESPONS BIBIT KAKAO (Theobroma cacao L.) ASAL SOMATIC EMBRYOGENESIS TERHADAP KOMPOSISI MEDIA TANAM YANG BERBEDA - Sari, Wulan Kumala (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2013)
One of the critical success cocoa cultivation is the use of quality plant materials. Cocoa plant material obtained through propagation techniques Somatic Embryogenesis (SE) is the latest method that can produce planlet that are the same with source, have a taproot and a branched structure similar with plant from seeds. Another advantage of this SE technique can be mass-produced seedlings, pest-disease free, growth is more uniform, more vigor, high yield and drought resistant. The objective of the experiment is to know the growth media composition which give the best effect on growth cacao seedling (Theobroma cacao L.) from Somatic Embryogenesis (SE). The experiment was conducted at The Agricultural Experiment Station of Agriculture Faculty, Padjadjaran University, Jatinangor, altitude ±700 m above sea level with soil type is Inceptisols. The experiment was conducted from June until October 2013, used Randomized Block Design (RBD), consisted of nine treatments combinations and replicated three times. The treatments were topsoil : casting (2 : 1) + urea 0,5 g application-1, topsoil : cattle dung (2 : 1) + urea 0,5 g application-1, topsoil : cacao pods compost (2 : 1) + urea 0,5 g application-1, topsoil : casting (2 : 1) + urea 0,75 g application-1, topsoil : cattle dung (2 : 1) + urea 0,75 g application-1, topsoil : cacao pods compost (2 : 1) + urea 0,75 g application-1, topsoil : casting (2 : 1) + urea 1 g application-1, topsoil : cattle dung (2 : 1) + urea 1 g application-1, topsoil : cacao pods compost (2 : 1) + urea 1 g application-1. The result of the experiment showed that the growth media composition consist of topsoil : casting (2 : 1) + urea 0,75 g application- 1 give better effect on vegetative growth of cacao seedling from SE compared to other treatment combinations, increased stem diameter, leaves number, shoot dry weight and total plant dry weight at 16 MST is 17,54g.